Peningkatan Pengetahuan Berbahasa Inggris kepada Anak-Anak Panti Asuhan Istana Yatim Al-Jufri - Titin Ervina; Agustino Agustino; Ellen Justine; Felix Putra; Jason Santoso; Nicoloas Nicoloas; Valens Tino; Yuky Yuky (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The implementation of increasing knowledge in English aims to improve foreign language skills and to build their awareness in learning English. This method of implementation begins with conducting site observations, then visiting the orphanage. we conducted interviews with the management at the Orphanage and also the children there about foreign language knowledge. After the interview we designed a service program to overcome the problem of carrying out socialization activities and motivating to build awareness that the importance of practicing foreign language skills. As a result of the program, we found that the children at the Orphanage still needed a lot of practice and we provided good self-study books for the future.